Eficácia de peixes larvófagos na redução de larvas de aedes aegypti em depósitos domiciliares com água - Cavalcanti, Luciano Pamplona de Goes (2009)
Dengue fever remains an important public health problem in northeast Brazil. Large domestic containers used to store water are important breeding sites of Aedes aegypti, the main vector. The use of alternatives to chemical vector control has increased in the last years. The objectives of this study were: to evaluate the inhibition of oviposition by female Ae. aegypti in domestic containers with larvivorous fish; to describe the survival of larvivorous fish to different chlorine concentrations; and to describe the efficacy of Betta splendens fish under field conditions. Oviposition was assessed in a cage of 6 m3 of size. The fish species Poecilia reticulata and B. splendens were used in the laboratory assays. In the cage, eight water containers were placed - four with fish, four without fish (control), and 100 mosquitoes. In each container with 15 l water eucatex strips were placed to facilitate oviposition. At the end of each week, eggs laid on these strips were counted. For each species, the assays were repeated for seven consecutive weeks. Survival of B. splendens and P. reticulata to different concentrations of chlorine (1.0, 1.5 and 2.0 mg / L) was assessed in drums with 35 liters of water. We used 105, 140 and 175 fish for each concentration: six test containers with chlorine for each control without chlorine. Secondary data of the Municipal Dengue Control Program of the city of Fortaleza were analyzed to assess the efficacy of B. splendens under field conditions. The presence of fish in household containers was verified after several weeks. Infestation of containers with mosquito larvae was compared to containers with the larvicide Bacillus thuringiensis israelensis. The presence of B. splendens inhibited oviposition by Ae. aegypti with an activity oviposition index of -0.627. The mean number of eggs laid in deposits with B. splendens (32.5 / week) was lower than in deposits with P. reticulata (200.5 / week) and controls (186.5 / week, p <0.0001). All B. splendens specimens survived a chlorine concentration of 1.0 mg / L, and 72.5% and 39.3% survived concentrations of 1.5 and 2.0 mg / L, respectively. On the other hand, only 4.4% of P. reticulata survived a concentration of 1.0 mg / L. Under field conditions, three containers were encountered with B. splendens and mosquito larvae (1.6%), significantly less than infested deposits with Bti (10.9%; p <0.001). In containers where the fish died or disappeared, infestation was 27.8% higher than in deposits with Bti (p <0.010). In deposits where the fish remained, efficacy was 85% better than Bti. The permanence of fish was higher in concrete tanks (48.5%), located outside the house (47.5%) and at ground level (53.3%). We conclude that B. splendens may be suitable for biological control of Ae. aegypti larvae in large domestic water containers